Automatic web services deployment - Ang, T.F.; Ling, T.C.; Phang, K.K.; Por, L.Y. (2009)
As web service has become the emerging paradigm,the area of web service research has received a lot of attention in recent years. Most of the web services are deployed by site administrators. As the number of request of web services increase tremendously, there is a need to replicate the services to multiple resources. Although manual deployment allow the services to be deployed safely, it is impossible to scale. To solve this problem, we propose in this paper a new architecture for automatic web services deployment. Through the experiment, we proved that automatic deployment strategy able to handle the increasing number of users’ request in an effective manner.